A new research on nomadic nations of Inner Asia - Tuguzhekova, Valentina N. (The New Research of Tuva, 2010)
Book review: Abayev N.V., Ayupov N.G. Ethnoecologic traditions of Turkic and Mongol nations in Tengriist and Buddhist civilizations of Inner Asia. Kyzyl: Tuvan State University Press, 2010 – 135 p.
Keywords: review; nomadic peoples; nematoidea; ecology; tradition; edition-2010; Asia-Central; tengrianstvo